Locations and Religious Factors Affecting Dengue Vectors in Nakhon Si Thammarat, Thailand - Siriwan WONGKOON; Mullica JAROENSUTASINEE; Krisanadej JAROENSUTASINEE (Walailak Journal of Science and Technology, 2011)
This study investigated the numbers of Aedes larvae found in relation to the religion of the people, the location of their houses, and the number of water containers in and around the house. We collected our questionnaire survey during April-May 2004 covering two different topographical areas (i.e. seaside and mountainous areas) and two religious factors (i.e. Buddhist and Muslims). We collected samples by using the stratified simple random sampling with a total of 400 households from all communities in 31 sub-districts. The results showed that there were a higher number of Ae. aegypti larvae in water containers in bathrooms, concrete tanks and large water jars than the number of Ae. albopictus larvae in both areas. Ae. albopictus larvae were found in higher numbers at the seaside area than in the mountainous area. On the other hand, the number of small water jars had a higher number of Aedes larvae in the mountainous area than in the seaside area. Considering only large water jars, covers apparently reduced the number of Ae. aegypti and other mosquito larvae. Regardless of the kind of cover, uncovered containers had more mosquito larvae than covered containers. More Ae. aegypti larvae were found in larger jars than in smaller jars and we also found more Ae. aegypti larvae in smaller jars which were <¼ full than at other water levels. There were three larval indices: Container Index (CI), House Index (HI) and Breteau Index (BI). All larval indices from our study indicated a high risk of Dengue Haemorrhagic Fever (DHF) transmission in both locations and religions. We found that HI in Muslim households was higher than in Buddhist households.